Effect of boric acid doped PEDOT:PSS layer on the performance of P3HT: PCBM based organic solar cells - Yagci, Ozlem; Yesilkaya, Serco Serkis; Yuksel, Sureyya Aydin; Ongul, Fatih; Varal, Nurhan Mehmet; Kus, Mahmut; Gunes, Serap; Icelli, Orhan (ELSEVIER SCIENCE SA, 2016)
In this study, we fabricated PEDOT:PSS film with different concentrations 0-5 mg/ml of boric acid (H3BO3) doped PEDOT:PSS film as hole collector layer. Undoped and boric acid doped PEDOT:PSS films are prepared with spin coating technique and characterized by XRD, UV, AFM, FTIR and electrical conductivity measurements. We fabricated polymer solar cells in the form of ITO/PEDOT:PSS:H3BO3/P3HT:PCBM/Al. Results show that the open-circuit voltage (V-oc) and the fill factor (FF) increased by introducing H3BO3 as dopant into the PEDOT:PSS layer due to an increase in the work function of PEDOT: PSS layer and improvement of surface roughness, respectively. The solar cells without H3BO3 showed a power conversion efficiency PCE of 1.79% whereas the cells with H3BO3 concentration of 1.25 mg/ml in PEDOT:PSS, showed a higher performance resulting in a PCE of 2.14% under AM 1.5G illumination. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: PEDOT:PSS; Bulk heterojunction solar cells; Boric acid; PHOTOVOLTAIC DEVICES; MORPHOLOGY; BLENDS; FILMS; CONDUCTIVITY; PEDOT/PSS; OXIDE; SPECTROSCOPY; EFFICIENCY; NANOTUBES; Materials Science; Physics; Polymer Science